2014
DOI: 10.1002/rcm.7027
|View full text |Cite
|
Sign up to set email alerts
|

GUMBOS matrices of variable hydrophobicity for matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: MALDI matrices of GUMBOS with tunable hydrophobicities are easily obtained simply by varying the counterion. We have found that hydrophobic matrix materials are very effective for MALDI determination of hydrophobic peptides and, similarly, the more hydrophilic peptides displayed greater intensity in the more hydrophilic matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(106 reference statements)
0
10
1
Order By: Relevance
“…To overcome this drawback, H.A. Ghafly et al [61] synthesized hydrophobic and crystalline matrix i. e. aminopyrene (AP)-based GUMBOS ( Figure 3) with different counter-anions such as Cl À , NTf 2 À and ascorbate (Asc À ). Firstly, GUMBOS [AP][Cl] was synthesized by treating AP and HCl in dichloromethane under stirring conditions for three hours.…”
Section: Synthesis and Applications Of Gumbosmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this drawback, H.A. Ghafly et al [61] synthesized hydrophobic and crystalline matrix i. e. aminopyrene (AP)-based GUMBOS ( Figure 3) with different counter-anions such as Cl À , NTf 2 À and ascorbate (Asc À ). Firstly, GUMBOS [AP][Cl] was synthesized by treating AP and HCl in dichloromethane under stirring conditions for three hours.…”
Section: Synthesis and Applications Of Gumbosmentioning
confidence: 99%
“…To overcome this drawback, H.A. Ghafly et al [61] . synthesized hydrophobic and crystalline matrix i. e. aminopyrene (AP)‐based GUMBOS (Figure 3) with different counter‐anions such as Cl − , NTf 2 − and ascorbate (Asc − ).…”
Section: Synthesis and Applications Of Gumbosmentioning
confidence: 99%
“…However, since the development of MALDI‐MS, only few matrices such as 2,5‐dihydroxybenzoic acid (DHB) or p ‐hydroxy‐α‐cyanocinnamic acid (HCCA) have found broad use for various analyte series . Therefore, research for new MALDI matrices has gained considerable interest during the last decade . Despite these notable efforts, it is still quite difficult to predict whether a compound will exhibit matrical properties or not, so the discovery of new matrices remains mostly empirical .…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, research for new MALDI matrices has gained considerable interest during the last decade. [9][10][11] Despite these notable efforts, it is still quite difficult to predict whether a compound will exhibit matrical properties or not, so the discovery of new matrices remains mostly empirical. 12 In this context, lichen metabolites may represent attractive candidates in the search for new matrix molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, CHCA-C3 was proposed to have high affinity with protein, so that the protein analyte could be tightly embedded in the matrix crystal and subjected to effective ionization without the interference of salt or wash process. Additionally, it has been reported that the increased affinity between matrix molecules and analyte could dramatically improve the detection sensitivity in MALDI-MS [49][50][51]. Therefore, though the detailed mechanism is not yet clear, the improved MALDI-MS performance for analysis of intact protein using CHCA-C3 matrix should be generally ascribed to high laser-induced ablation ability, even-distributed matrixanalyte co-crystal, and increased affinity for protein.…”
Section: Mechanism Analysismentioning
confidence: 99%